STUDI PENGARUH PERLAKUAN ALKALI TERHADAP SIFAT MEKANIK DAN MORFOLOGI KOMPOSIT SERAT PELEPAH KELAPA SAWIT BERMATRIK UREA FORMALDEHIDA - Istana, Budi; Utami, Lega Putri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Palm frond residue is one of the valuable wastes from palm oil plantations. This refuse can be repurposed and transformed into materials for producing acoustic composites. This study investigates the mechanical and morphology characteristics of a composite material reinforced with natural fiber palm fronds and a urea-formaldehyde (UF) as a matrix. Two parameters are formulated: the effect of alkali treatment on the fiber and the effect of density. The treatment parameter refers to the particles without treatment, 60 and 180 minutes of 2% alkaline immersion. Composite densities were determined with 0.4, 0.5, and 0.6 g/cm3. The composite was made using hot pressed at a pressure of 1.8 MPa, a temperature of 140OC for 5 minutes with 10% Urea Formaldehyde resin. Alkaline treatment and density of composite have a significant effect on mechanical and morphological characteristics. The best mechanical characteristics were obtained from panels with a 0.6 g/cm3 density, without treatment, MOE: 533.53 N/mm2. The results of this study have the potential to lead to the use of sustainable palm oil waste materials in novel products, which has a significant impact and great relevance not only from environmental aspects but also from social and economic aspects in Indonesia.